Development of environmental management accounting system: a conceptual approach - Medeckytė, Kamilė; Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2023)
With the rise of environmental problems caused by human activities, such as misuse of natural resources, rapid deforestation, and discharge of radioactive and other chemical waste into water bodies, soil and the atmosphere, environmental management accounting has emerged as a tool for promoting sustainable development and reducing negative environmental impacts in businesses. This area of accounting provides a means for analyzing, assessing, controlling, and managing the environmental performance of companies. However, there is a dearth of studies in the scientific literature that systematically assess the potential for introducing and developing environmental management accounting in an enterprise. Therefore, this study aims to identify the areas, instruments, outcome, impact measures, and other elements of environmental management accounting, and integrate them in a targeted manner to develop a conceptualized environmental management accounting system. The results of the literature review and systematic analysis are summarized to provide a conceptual framework for an environmental management accounting system consisting of the following elements: 1) objectives; 2) inputs; 3) processes; 4) outputs/outcomes; 5) feedback; and 6) external environmental conditions. The introduction of such a system would improve the development of environmental management accounting for the long-term sustainability and eco-efficiency of companies.